Amelia Earhart [videorecording (DVD)] : queen of the air - Orkin, Sanford (A & E Home Video ; Distributed by New Video, 2010)
A look at this groundbreaking aviator and her mysterious disappearance during her 1937 flight around the world, through interviews, newly discovered evidence, and extensive archival footage.